Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1111/ocr.12105
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional analysis of palatal shape in patients treated with SARME using traditional and geometric morphometrics

Abstract: Dense surface model provided descriptive visualization of the treatment effect and was helpful in the evaluation of palatal shape variability including detection of the most difficult patients. Correction of the dental arch width discrepancy by SARME was successfully achieved. After therapy, palatal shape variability of most of the patients was comparable to the variability of the control group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…Ultimately, after undergoing a comprehensive assessment based on the predetermined inclusion criteria, a total of 7 articles were deemed eligible and subsequently included in the final analysis [9,11,[14][15][16][17][18]. The other 19 articles were excluded due to the following reasons: nine lacked maxillary cephalometric measurements [8,13,[20][21][22][23][24][25][26]; three were focused on nonsurgical RPE [27][28][29]; three included patients with orthodontic tooth movement between the two time points of obtaining radiological images [10,30,31]; two were systematic reviews [32,33]; one was reported again in a later study by the same team [34]; and one was a case series with limited sample size [35]. The PRISMA flowchart of the article inclusion and exclusion screening is shown in Figure 1.…”
Section: Literature Searching and Study Selectionsmentioning
confidence: 99%
“…Ultimately, after undergoing a comprehensive assessment based on the predetermined inclusion criteria, a total of 7 articles were deemed eligible and subsequently included in the final analysis [9,11,[14][15][16][17][18]. The other 19 articles were excluded due to the following reasons: nine lacked maxillary cephalometric measurements [8,13,[20][21][22][23][24][25][26]; three were focused on nonsurgical RPE [27][28][29]; three included patients with orthodontic tooth movement between the two time points of obtaining radiological images [10,30,31]; two were systematic reviews [32,33]; one was reported again in a later study by the same team [34]; and one was a case series with limited sample size [35]. The PRISMA flowchart of the article inclusion and exclusion screening is shown in Figure 1.…”
Section: Literature Searching and Study Selectionsmentioning
confidence: 99%
“…GMM is the statistical analysis of shape and size features, including pathologies, as they describe configurations of landmark points in two or three dimensions. Well established in anthropology (Weber & Bookstein, ) and paleobiology (Lawing & Polly, ), this method is increasingly being used in fields of medical research such as orthodontics (Bertl et al, ; Celar, Freudenthaler, Celar, Jonke, & Schneider, ), anatomy (Loth et al, ), psychology (Prasad et al, ), and craniofacial surgery (Segna et al, ; Trefný, Krajíček, & Velemínská, ). In earlier applications to mouse models, GMM has led to discoveries in ontogenetic development (Boughner et al, ), quantitative trait locus effects (Workman, Leamy, Routman, & Cheverud, ), relationships between gene and pathology (Green et al, ) and similarity of developmental processes to those of humans (Martínez‐Abadías et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In the field of congenital pathological abnormalities, the 3D approach was used to explore the metrical modifications of cleft palate [13][14][15]. Other applications in orthodontics concern the assessment of palatal linear modifications after maxillary expansion therapy [16][17][18]. The main use of the novel technologies relies on the metrical assessment of different parameters, be they linear distances, surfaces or volumes: however, another important tool concerns the chance of superimposing 3D models [11].…”
Section: Introductionmentioning
confidence: 99%